Risk assessment of recreational use watercourses Kharkiv region as an important indicator of quality index of life - Рибалова, Ольга Володимирівна; Варивода, Євгенія Олександрівна; Бєлан, Сергій Володимирович (Eastern-European Journal of Enterprise Technologies, 2012)
This paper include new approach for assessing the appropriateness of the potential risk of public health and proposed to use this indicator to evaluate the quality of life in order to determine the danger level of recreational water use and the potential for environmental emergencies